2003
DOI: 10.1057/palgrave.jors.2601635
|View full text |Cite
|
Sign up to set email alerts
|

A new hybrid genetic algorithm for the capacitated vehicle routing problem

Abstract: Abstract.Recently proved successful for variants of the vehicle routing problem (VRP) involving time windows, genetic algorithms have not yet shown to compete or challenge current best search techniques in solving the classical capacitated VRP. In this paper, a hybrid genetic algorithm to address the capacitated vehicle routing problem is proposed. The basic scheme consists in concurrently evolving two populations of solutions to minimize total traveled distance using genetic operators combining variations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 25 publications
(39 reference statements)
0
28
0
Order By: Relevance
“…Starting from the solutions provided by Fu et al [91], for instance C5 with 17 vehicles LSA found a solution of cost 868. 44 32 and ttime avg (0.7) = 460.0. As expected, the average CPU time consistently increases with the number of extracted customers, while the best solution costs are obtained with the default setting of p (i.e., p = 0.5), thus indicating that extracting too many customers leads in general to worse solutions (i.e., z avg (0.7) > z avg (0.5)).…”
Section: Computational Resultsmentioning
confidence: 99%
“…Starting from the solutions provided by Fu et al [91], for instance C5 with 17 vehicles LSA found a solution of cost 868. 44 32 and ttime avg (0.7) = 460.0. As expected, the average CPU time consistently increases with the number of extracted customers, while the best solution costs are obtained with the default setting of p (i.e., p = 0.5), thus indicating that extracting too many customers leads in general to worse solutions (i.e., z avg (0.7) > z avg (0.5)).…”
Section: Computational Resultsmentioning
confidence: 99%
“…The search space can also be reduced by means of representations that do not allow certain solutions [60,135] or by using a heuristic approach that removes some unreasonable solutions [3]. Many other examples can be found in the literature [7,11,43].…”
Section: Model Restriction and Reducing The Search Spacementioning
confidence: 99%
“…Table 6 provides a comparison on the results obtained on the fourteen classical instances by some recent metaheuristics for the VRP (the reader is referred to Gendreau et al (2002), and for more results and comparisons). These are Cordeau et al (2002), Toth and Vigo (2003), Berger and Barkaoui (2003), Prins (2004), Tarantilis (2004) and TS + PR (columns marked CGLPS, TV, BB, P, T and HG). The results are expressed in terms of total distance traveled.…”
Section: Computational Experimentsmentioning
confidence: 99%
“…While many heuristic approaches have been used to successfully tackle the VRP during the past five decades (Alfa et al 1991, Kawamura et al 1998, Bullnheimer et al 1998, Bullnheimer et al 1999, Reimann et al 2004, Berger and Barkaoui 2003, Prins 2004, Tarantilis 2004, Tabu Search (TS) has been the most widely applied technique to provide good approximate solutions for the problem. This method was originally proposed by Glover (1986) as a local search technique that does not terminate when it encounters local optima, but rather proceeds with moves that degrade the objective function.…”
Section: Introductionmentioning
confidence: 99%